Perceived Determinants of Health-Related Behaviors Among Patients with Coronary Heart Disease After Percutaneous Coronary Intervention: A Longitudinal Qualitative Study - Su X; Zhang Y; Zhou H; Ma F; Jin X; Bai Y; Wei W; Zhang X; Zhou M (Patient Preference and Adherence, 2024)
Xu Su,1,* Yimei Zhang,1,* Huilin Zhou,1 Fang Ma,1 Xiaorong Jin,1 Yangjuan Bai,2 Wei Wei,3 Xiong Zhang,1 Min Zhou1 1Department of Nursing, The First Affiliated Hospital of Kunming Medical University, Kunming, People’s Republic of China; 2Cardiology Department, The First Affiliated Hospital of Kunming Medical University, Kunming, People’s Republic of China; 3Digestive Surgery Department, The First Affiliated Hospital of Kunming Medical University, Kunming, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Ma, Department of Nursing, The First Affiliated Hospital of Kunming Medical University, No. 295, Xichang Road, Kunming, 650032, People’s Republic of China, Email rebeccamalei@126.comPurpose: Studies had reported some influencing factors of health behavior among patients with coronary heart disease(CHD) after percutaneous coronary intervention(PCI). However, considering that human perceptions are complex, unrestricted and dynamically changing. A longitudinal qualitative study was conducted to explore the determinants of health-related behaviors of patients after PCI and dynamic changes of these determinants at the 1st, 3rd, and 6th months.Patients and Methods: Using purposive sampling, 18 patients undergoing PCI were interviewed. The conventional content analysis method was used to identify categories and subcategories. Semi-structured, face-to-face or telephone in-depth interviews were conducted at the cardiology unit of a tertiary referral hospital in Yunnan Province, China from March 2022 to January 2023.Results: Seven categories with some subcategories were constructed from the data, categorized into three domains. Firstly, individual factors include (i) Personal coping with healthy lifestyle requirements (tried but failed; I can do it), (ii) individual perception and feeling toward disease (knowing about the disease; belief of cure; fears of relapse), and (iii) personal benefits (improved health; meaning of life). Secondly, social factors include (i) social facilitators (family resources; healthcare support), (ii) social barriers (inconvenient medical care service; conflicting information). Finally, cultural factors include (i) way of living (dietary habits; key roles of yan (cigarette) and jiu (alcohol) in Chinese society), (ii) way of thinking (fatalism and Confucian familism).Conclusion: The determinants of health-related behaviors of patients after PCI are multifaceted and dynamic. Different interventions should be formulated to promote patients’ adherence to health behaviors. Moreover, priority should be given to the impact of traditional Chinese philosophy on the health behaviors of patients after PCI, and the health promotion program for these patients should be culturally sensitive. In addition, future research should further explore the determinants of health behaviors among diverse ethnic minorities after PCI, which has not been fully inquired in this study.Keywords: coronary heart disease, percutaneous coronary intervention, health behavior adherence, qualitative research, Chinese traditional culture